The American psychological Association's practice guidelines for men and boys: Are they hurting rather than helping male mental wellness?. (January 2023) - Ferguson, Christopher J.
Abstract: Introduced in 2018, the American Psychological Association's (APA) Practice Guidelines for Men and Boys was intended to provide helpful direction for practitioners when seeing male patients. This followed in the tradition of other practice and clinical guidelines for clinical work with specific identity populations. However, the practice guidelines for men and boys quickly became controversial given concerns that the guidelines were disparaging of men and boys, particularly those with traditional values and sought to impose progressive or feminist gender norms and ideologies rather than remaining focused on clinical wellness and empathy. This review finds that, though the guidelines were offered in good faith, many of the critiques are likely valid. Specifically, the guidelines failed to acknowledge significant evidence for biological influences on gender (e.g., hormonal, and hypothalamic influences on gender identity and gendered behavior), were unintentionally disparaging of traditional men and families, and were too closely wedded to specific sociocultural narratives and incurious of data not supporting those narratives. It is concluded that there are reasonable concerns that the current guidelines may do more harm than good by dissuading traditional men and families from seeking counseling.